Ultrasound Assistance for Central Venous Catheter Placement in a Pediatric Emergency Department Improves Placement Success Rates. (September 2014) - Gallagher, Rachel A.; Levy, Jason; Vieira, Rebecca L.; Monuteaux, Michael C.; Stack, Anne M.; Moore, Chris
Abstract Objectives The use of ultrasound (US) has been shown to improve success rates and reduce complications of central venous catheter (CVC) placement in adult emergency department (ED) patients. The authors sought to determine if US assistance for CVC placement is associated with an increased success rate in pediatric ED patients. Methods This was a retrospective cohort study of CVC placement in a pediatric ED from January 2003 to October 2011. Data were extracted from a procedure log created to record details entered by physicians at the time of CVC placement, including indication, location, complications, and information regarding use of US. All femoral vein and internal jugular vein CVC placement attempts performed by, assisted with, or directly supervised by pediatric emergency physicians (EPs) were included. Characteristics of procedures performed with and without US assistance were compared, controlling for patient and physician factors. The primary outcome was the success rate of CVC placement. Results There were 168 patients undergoing CVC placement attempts. The proportion of successful placement attempts was significantly higher when using US assistance (96 of 98) compared to those without (55 of 70; 98% vs. 79%, odds ratio [OR] = 13.1, 95% confidence interval [CI] = 2.9 to 59.4). When controlling for patient‐ and physician‐specific factors, success rates remained significantly higher. Conclusions Ultrasound assistance was associated with greater likelihood of success in CVC placement in a pediatric ED.